Additional Dialogue by… Versions of Shakespeare in the World’s Multiplexes - Paterson, Ronan (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
William Shakespeare has been part of the cinema since 1899. In the twentieth century almost a thousand films in some way based upon his plays were made, but the vast majority of those which sought to faithfully present his plays to the cinema audience failed at the box office. Since the start of the twenty-first century only one English language film using Shakespeare’s text has made a profit, yet at the same time Shakespeare has become a popular source for adaptations into other genres. This essay examines the reception of a number of adaptations as gangster films, teen comedies, musicals and thrillers, as well as trans-cultural assimilations. But this very proliferation throws up other questions, as to what can legitimately be called an adaptation of Shakespeare. Not every story of divided love is an adaptation of Romeo and Juliet. Different adaptations and assimilations have enjoyed differing degrees of success, and the essay interrogates those aspects which make the popular cinema audience flock to see Shakespeare in such disguised form, when films which are more faithfully based upon the original plays are so much less appealing to the audience in the Multiplexes.